Penerapan Model Project Based Learning Berbasis DGMATH untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Prianggono, Agus; Yuniarti, Dwi Ariani; Pawening, Ari Setiyani (Edumatica : Jurnal Pendidikan Matematika, 2023)
Learning mathematics for students at the elementary school level is an important lesson to be concern. Learning model to use is a student centered learning model. DGMATH-based PBL is a student centered learning model and uses a DGMATH application that contain main subject is elementary arithmetic. The purpose of this study was to test the effectiveness of DGMATH-based PBL learning and measure how much influence student motivation had on learning outcomes from the implementation of DGMATH-based PBL learning. The method used is a quantitative method to test the effectiveness and regression test to learning motivation on DGMATH-based PBL learning with the subject of first grade students (1) SD Islam Insan Cendekia with a total of 60 students. The instruments used were learning tools, pre-test questions, post-test questions and student learning motivation questionnaires. The research results showed that in the completeness test the results were 82.83 in DGMATH-based PBL learning and in the average difference test with a sig value of 0.015 <0.05, which means that there is a significant difference in learning outcomes between the experimental class and the control class. So it can be concluded that DGMATH-based PBL learning has proven effective and learning motivation has an influence of 76% on learning outcomes.